Adaptation and dispersal of anatomically modern humans in a changing environment in North Africa: the contribution of microvertebrates - (:unkn) unknown (My University, 2016)
There is little data available on the environmental context of the arrival of the first anatomically modern humans in North Africa, and subsequent Palaeolithic and Neolithic occupations within this region. Microvertebrates such as rodents, shrews, amphibians and squamates are known to be good indicators of climate and landscape changes. They also represent continental paleoecological records that can be directly related to human occupations. Moreover, faunas and humans have been subjected to several dispersion waves through similar routes, and some rodents may present anthropophilous behavior. Therefore, by understanding the migration pathways of these microvertebrates, it is possible to propose scenarios for human dispersion events. In this study we consider the rich microfaunal assemblages from the Temara region (Atlantic Morocco), and focus particularly on the rodent Arvicanthis sp. This rodent is currently found in sub-Saharan savannah, however it is known to have made occasional incursions into North Africa throughout the Pleistocene. This raises questions concerning the exact species, origin and route taken by this taxon to reach northern Morocco, which probably occurred during wetter periods when the Sahara was not acting as an arid barrier. It is particularly interesting because some species belonging to the genus Arvicanthis are today considered anthropophilous and live near human habitations in sub-Saharan Africa. We propose that small animals should be used as markers of palaeoenvironmental and migration history offauna and humans during the Pleistocene and the Holocene in North Africa.
Keywords: African Research